INTEGRATING STUDENTS WITH SPECIAL NEEDS IN PHYSICAL EDUCATION CLASS - SCIENTIFIC CONCERNS - Cotos Florin; Bogdan-Constantin Ungurean (Sport şi Societate)
The aim of the study was to analyze the way in which the topic of integration of children with Special Educational Needs (SEN) in physical education class is approached in the specialized literature.Analyzing over 65 scientific papers published in prestigious journals reveals researchers' efforts to identify and address the integration issues of children with SEN. The research topics addressed cover a wide range of issues related to the integration of children with SEN, with solutions far from being exhausted. The present study identified three main themes addressed in the analyzed studies: the importance of physical education classes in integrating children with SEN, the importance of physical education teacher involvement in integrating children with SEN, and the need of ensuring an appropriate regulatory framework.